Using Augmented Reality to Improve Learning Efficacy in a Mechanical Assembly Course - Han, Peng-Fei; Zhao, Feng-Kui; Zhao, Gang (IEEE transactions on learning technologies, 2022)
Mechanical assembly courses are widely set up for mechanical and vehicle engineering majors. Teaching in these classes is traditionally presented in the form of 2-D lectures, which are ineffective for students to understand complex 3-D information. The study presented in this article aimed to investigate whether augmented reality (AR) could improve students' learning efficacy in a mechanical assembly course. An AR-based assembly instruction app on mobile devices was developed, and a comparative research approach was adopted. A total of 104 junior students from four classes on automotive engineering at Nanjing Forestry University participated in the experiment during their professional skill training course. The control group was provided with handouts as usual, and the experimental group was required to use AR instructions during the assembly processes. Several evaluation indicators, such as assembly quality and speed, were recorded and analyzed at the same time. The results showed that such indicators were significantly improved with the utilization of AR. In addition, a questionnaire was specifically designed and distributed to all the students at the end of the course. It was found that several learning factors, such as learning interest and academic achievements in the experimental group, showed a positive correlation.